VISUAL ANALYSIS OF THE CHARACTER MIYAMOTO MUSASHI IN THE COMIC "VAGABOND" BY TAKEHIKO INOUE - Mukti, Indra Awaludin; Kasmana, Kankan (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
Vagabond comics, based on Musashi novels, depict the world of Japanese samurai in a realist and naturalist style, featuring protagonists like Miyamoto Musashi. Created by Takehiko Inoue, the comic blends action, drama, and seinen with detailed depictions of characters and settings. This research focuses on the character of Miyamoto Musashi in Vagabond volume 34 page 146 when Musashi is splitting water with his sword. This research uses descriptive research, data collection through non-participant observation, documentation, and literature study. This study aims to analyze the visualization of Miyamoto Musashi's character in Vagabond comic volume 34 page 146 when Miyamoto Musashi is splitting water using his sword skills. The results of the analysis show that Miyamoto Musashi on volume 34 page 146 is depicted with realist and detailed expressions and gestures ranging from hair, eyebrows, eyes, nose, beard, lips, gestures, to water movements. The research is useful to know how the visualization of characters and scenes in the Vagabond comic volume 34 page 146 can be depicted with realistic and detailed